Long‐term mammal and nocturnal bird trends are influenced by vegetation type, weather and climate in temperate woodlands. (21st July 2020) - Lindenmayer, David B.; Lane, Peter; Westgate, Martin J.; Scheele, Ben C.; Crane, Mason; Florance, Daniel; Crane, Clare; Smith, David
Abstract: Many studies have documented the individual effects of variables such as vegetation, long‐term climate and short‐term weather on biodiversity. Few, however, have explicitly explored how interactions among these major drivers can influence species abundance. We used data from a 15‐year study (2002–2017) in the endangered temperate woodlands of south‐eastern Australia to test hypotheses associated with the effects of vegetation type, long‐term climate and short‐term weather on population trajectories of seven species of (largely) nocturnal mammals and birds. Despite prolonged drought conditions, there was a significant increase in the abundance of some species over time (e.g. the Eastern Grey Kangaroo). It is possible that destocking of domestic livestock may have reduced competition with Kangaroos, thereby facilitating increases in abundance. The Common Brushtail Possum and Common Ringtail Possum were significantly less likely to occur in replanted woodlands, possibly because of the paucity of nesting sites. We found no evidence that replanted woodlands are refuges for exotic pest species like the European Rabbit and Red Fox. Short‐ and long‐term rainfall and vegetation type had important independent and combined effects on animal abundance. That is, responses to periods of high short‐term rainfall were dependent on vegetation type and whether sites occurred in long‐term climatically wet versus climatically dry locations. For example, the Red Fox responded positively to high levels of short‐term rainfall, but only at climatically dry sites. Our results highlight the complementary value of different vegetation types across the landscape and the context‐specific responses of animals to short‐term fluctuations in moisture availability. They also underscore the value of long‐term monitoring at a landscape scale for examining how multiple interacting factors influence trends in animal abundance.